Multifunctional PANI/MnO2- Decorated Polystyrene Composite Nanofibers for Oil Adsorption and Organic Dye Removal - Hemalatha Parangusan (6556133) (2025)
The development of multifunctional materials is essential for the effective treatment of compounds containing both water-soluble dye and water-insoluble oils. In this work, PANI/MnO2-decorated polystyrene nanocomposite fibers were synthesized by using the chemical polymerization technique. The structural, thermal, and morphological properties of the prepared sample are investigated using XRD, FTIR, thermogravimetric, and SEM analysis. PANI/MnO2 nanoparticles were found to be coated on the surface of polystyrene fibers, based on SEM analysis. Contact angle studies are performed to investigate the surface properties and the influence of nanofillers on the surface wettability. The PS/PANI-MnO2 nanocomposite fiber shows a contact angle of 141.4° compared to the 101.2° of the neat PS fibers, evidencing the hydrophobicity. Also, the coated fibers possess an excellent photocatalytic ability that can be used to break down the dye molecules and absorption of oil pollutants from the wastewater. The photocatalytic degradation of azocarmine G dye by using PS/PANI-MnO2 nanocomposite fibers shows 94% of AZG dye degraded within 120 min. The ability of the composite fiber to absorb oil was enhanced by the addition of PANI/MnO2 nanofiller. The results show that the fabricated composite fibers can be used to degrade organic pollutants and adsorb oil. This low cost, reusability, and easy operation of the PS/PANI-MnO2 fiber mats make them potentially beneficial for wastewater treatment. Other Information Published in: Water Conservation Science and Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41101-025-00367-y